Pola Frekuensi Kebutuhan Air Irigasi pada beberapa Penggunaan Lahan dengan Teknologi Otomatisasi Monitoring Pengendalian Kelembaban Tanah berbasis Sensor Dielektrik - Putri, Elsa Lolita; Fitriani, Nur; Hermawan, Bandi; Herman, Welly (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2022)
Indonesia is an agrarian country and requires the development of improvements in soil productivity. The decline in soil productivity for agriculture is currently caused by several factors, namely land conversion to a decrease in the quantity of ground water. The actual frequency pattern of irrigation water needs with the application of dielectric sensor technology is carried out in cultivation in order to create efficiency in the provision of irrigation water. This research was conducted using a single factor experimental method with repeated measurements on three types of land use, namely land without vegetation, soil with grass vegetation, and soil with tomato cultivation. Measurements were carried out using an automated application of soil moisture monitoring based on dielectric technology with two measuring periods. Each measuring period consists of two weeks or fourteen days. Soil sample analysis was carried out at the Bengkulu University soil laboratory. The results of the observations were analyzed using variance (ANOVA) on the 5% F test table, the BNT test was carried out at the 5% level on data that had a significant effect. The results showed that the frequency of giving irrigation water on the 1st day to the 14th day in the 2 observation periods on the Bera land was the most common compared to the use of grass vegetated land and the use of tomato cultivation land, which was 5 times in the 1st and 4th periods. times in the 2nd period with 14 days each. Provision of irrigation water will stop automatically when the dielectrometer shows the field capacity so that it can show the frequency of giving different water to each field.Key words : Dielectric; Frequency; Irrigation water